2022
DOI: 10.2174/18742858-v16-e221128-2022-14
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Evaluation of Four Selected Medicinal Plants against Staphylococcus aureus Isolated from Bovine Mastitis in Mieso District West Hararghe Zone, Oromia Regional State, Ethiopia

Abstract: Background: Bovine mastitis is a major disease mostly caused by bacterial infection and associated with losses in the global dairy industry. Since mastitis-causing bacterial developing multidrug resistance to conventional antibiotics, there is an admirable supplementary study on medicinal plants to use them as an alternative therapy. This study aimed to evaluate the antibacterial activity and phytochemical screening of four selected medicinal plants against Staphylococcus aureus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, the plant demonstrates moderate antibacterial activity against E. coli and P. aeruginosa isolates. The present study's observed MIC values for plant crude extracts fall within the range or are less than those of other plant extracts reported from various nations (Manilal et al., 2020; Popović et al., 2015; Sama et al., 2015; Yirdaw & Kassa, 2023; Yusuf et al., 2022). The MIC of B. abyssinica extracts reported by Ameya et al.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the plant demonstrates moderate antibacterial activity against E. coli and P. aeruginosa isolates. The present study's observed MIC values for plant crude extracts fall within the range or are less than those of other plant extracts reported from various nations (Manilal et al., 2020; Popović et al., 2015; Sama et al., 2015; Yirdaw & Kassa, 2023; Yusuf et al., 2022). The MIC of B. abyssinica extracts reported by Ameya et al.…”
Section: Resultssupporting
confidence: 57%
“…The present study's observed MIC values for plant crude extracts fall within the range or are less than those of other plant extracts reported from various nations (Manilal et al, 2020;Popović et al, 2015;Sama et al, 2015;Yirdaw & Kassa, 2023;Yusuf et al, 2022). The MIC of B. abyssinica extracts reported by Ameya et al (2019) was significantly higher (12.5-25 mg/mL) than the current finding (0.78-3.12 mg/mL).…”
Section: Minimum Inhibitory Concentrations and Minimum Bactericidal C...contrasting
confidence: 54%
“…After the MIC determination of the AgNO 3 , OTC, AgNPs and Ag-OTC-Ns, aliquots of 10 µl samples from all the tubes which showed no visible bacterial growth, were seeded on Brain Heart Infusion Agar (BHI agar) plates and incubated for 24 h at 37 °C. When 99.9% of the bacterial population is killed at the lowest concentration of an antimicrobial agent, it is termed as the minimum bactericidal concentration (MBC) endpoint (Yusuf et al 2022). This was done by observing pre and post-incubated agar plates for the presence or absence of bacterial colonies.…”
Section: Determination Of Mbcmentioning
confidence: 99%
“…The rise of antibiotic resistance hence needed a remedy in the form of some other alternatives besides conventional antibiotics and the best of these turned out to be plant extracts (Zaatout 2022). An important reason for using plant extracts was their easy availability and affordability (Rakholiya et al 2013;Yusuf et al 2022). This chapter aims to explain antibiotic resistance in some important pathogens of mastitis along with its causes, effects, and treatment.…”
Section: Introductionmentioning
confidence: 99%